2022
DOI: 10.3389/fspas.2022.1063329
|View full text |Cite
|
Sign up to set email alerts
|

Using MEPED observations to infer plasma density and chorus intensity in the radiation belts

Abstract: Efforts to model and predict energetic electron fluxes in the radiation belts are highly sensitive to local wave-particle interactions. In this study, we use multi-point measurements of precipitating and trapped electron fluxes to investigate the dynamic variation of chorus wave-particle interactions during the 17 March 2013 storm. Quasilinear theory characterizes the chorus wave-particle interaction as a diffusive process, with the diffusion coefficients depending on the particle energy and pitch angle, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These coefficients are calculated using quasilinear theory, with the chorus wave intensity estimated from National Oceanic and Atmospheric Administration (NOAA) Polar Orbiting Environmental Satellites (POES) measurements of precipitating and trapped electron fluxes using the method in and Ni et al (2014). The diffusion coefficients used in this study do not include the effects of a changing ω pe /ω ce ratio, which can substantially affect the wave power estimated from POES observations (Longley et al, 2022). The set of coefficients in Ma et al (2018) are calculated separately for upper and lower band chorus with Gaussian frequency and wave normal angle distributions in each band.…”
Section: Chorus Wave Diffusion Coefficientsmentioning
confidence: 99%
“…These coefficients are calculated using quasilinear theory, with the chorus wave intensity estimated from National Oceanic and Atmospheric Administration (NOAA) Polar Orbiting Environmental Satellites (POES) measurements of precipitating and trapped electron fluxes using the method in and Ni et al (2014). The diffusion coefficients used in this study do not include the effects of a changing ω pe /ω ce ratio, which can substantially affect the wave power estimated from POES observations (Longley et al, 2022). The set of coefficients in Ma et al (2018) are calculated separately for upper and lower band chorus with Gaussian frequency and wave normal angle distributions in each band.…”
Section: Chorus Wave Diffusion Coefficientsmentioning
confidence: 99%
“…We see a clear improvement in our results, for both >30 keV (black crosses) and >100 keV (blue triangles) energy channels when we decrease the plasma density used in the calculation of the chorus-driven diffusion caused precipitation. This suggests the density used within the BAS model may be too high; similarly, Longley et al (2022) used the ratio between the precipitating and trapped flux observed by POES on 17 March 2013 to infer a generally lower plasma density than used in BAS-RBM. The next improvement in correlation values seen in Figure 13 comes from using solely RBSP data (as opposed to the averaging approach employing the entire BAS wave data base) to calculate the diffusion coefficients, almost doubling the correlation coefficient for the higher energy channel from 0.25 to 0.46.…”
Section: Discussionmentioning
confidence: 99%
“…However, the bounce-averaged diffusion coefficients used in Chan et al (2023), were computed using a dipolar magnetic field and a static density distribution. The diffusion coefficients, therefore, did not exhibit a realistic variability due to either the storm-time magnetic field or the cold plasma density, which can significantly affect both the estimated wave power (Longley et al, 2022) and the characteristics of the wave-particle interactions themselves (e.g., Kennel & Petschek, 1966).…”
Section: Introductionmentioning
confidence: 99%